Social Support as a Coping Mechanism for Fatherless Adolescents: Dukungan Sosial Sebagai Mekanisme Coping untuk Remaja Fatherless - Rahmasari, Diana; Rachmawati, Tasya Saecarya; Darmawanti, Ira; Oktaviana, Mimbar (Universitas Muhammadiyah Sidoarjo, 2024)
Family is a place where children get affection and develop. In order to grow well, children need affection from their mother and father. In reality, there are families that do not get the role of father, which is called fatherless. The condition of fatherless has an impact on themself. In order for the impact not interfere with their activities, children need to make various efforts called coping strategies. To get a adaptive coping strategy, it is necessary to have supportive social support. This study is a qualitative research conducted on two adolescents and the goal is to find out how the role of social support with coping mechanisms that arise in children who experience fatherlessness. The result of this study was that participants carried out emotion-focused coping with a lot of influence by social support.